Enhancing the Antiproliferative Activity of Perillyl Alcohol against Glioblastoma Cell Lines through Synergistic Formulation with Natural Oils - Alharbi, Waleed S.; Alshehri, Abdullah A.; Ahmed, Tarek A.; Md., Shadab; Almehmady, Alshaimaa M.; Alshabibi, Manal A.; Altamimi, Reem M.; El-Say, Khalid M. (Current Pharmaceutical Design, 2024)
Background: Due to its volatility, photostability, and gastrointestinal toxicity, Perillyl Alcohol (POH), a monoterpenoid component of various plant species, is a chemotherapeutic drug with insufficient efficacy. Many naturally occurring bioactive compounds have well-known antiproliferative properties, including sefsol, jojoba, tea tree, and moringa oils. Objective: This study sought to develop an oil-based Self Nanoemulsifying Drug Delivery System (SNEDDS) using tween 80 as the surfactant and Dimethyl Sulfoxide (DMSO) or Polyethylene Glycol (PEG) 400 as the cosurfactant; the oils were used in a range of 10-20% to boost POH's anticancer efficacy. Methods: The formulations' size, charge, and impact on the viability of glioma cell lines, ANGM-CSS and A172, were evaluated. Results: The developed SNEDDS formulations ranged from 3 nm to 362 nm in size, with electronegative surface charges between 5.05 and 17.0 mV and polydispersity indices between 0.3 and 1.0. Conclusion: The findings indicated that the antiproliferative effect of POH-loaded Nanoemulsion (NE) could be used as a possible anticancer therapy for glioblastoma in vitro, particularly when paired with the tested natural oils. Before asserting that this delivery technique is appropriate for glioblastoma therapy, additional in vitro and in vivo investigations are required.
Keywords: glioblastoma A172 cells